Dual Education And Youth In The Education System In Uzbekistan - Turamurodov Ulugbek (Peerian Journals Publishing, 2022)
As each society marks its own path of development, of course, it also pays special attention to the upbringing of young people who are the flower and trust of the country. In general, since the beginning of mankind, the upbringing of children has been carried out in one way or another. In the time of the primitive community, this process may have taken place sometimes consciously and sometimes unconsciously. In any case, the methods of upbringing have been constantly evolving, and as time has passed, as life has become more complex, they have taken on a deeper and broader meaning. In general, education has not escaped the attention of the people. This means that from ancient times the upbringing of children has played an important role in human life. Every parent wants their child to grow up to be a smart, polite, kind, hard-working person, and the precious power tries to create conditions for it, to see its perfection, the fruit of its labor. The success of his offspring will not spare his strength or, if necessary, his life in the way of his future
Keywords: complex; ancient; upbringing; offspring